The Influence of Social Media Public Relations on Bincang Perempuan Media Image among Generation Z - Elsabila Larasati; Retno Rahma Putri; Ranggi Dwi A; Vincensius F S (Journal of Law, Social Science, and Management Review, 2026)
This study is motivated by the growing role of social media as a digital public relations space in shaping public perception toward media organizations. Bincang Perempuan, as a digital platform focusing on women's issues, lifestyle, and education, requires communication management that is informative, interactive, consistent, creative, and capable of engaging young audiences. This study aims to analyze the influence of Social Media Public Relations on the Media Image of Bincang Perempuan among Generation Z. The research uses an explanatory quantitative approach with a survey method through a Likert-scale questionnaire. The population consisted of 80 students from the Communication Science Study Program, class of 2023, in classes A1, A2, and A3, with a sample of 49 respondents. The data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) through SmartPLS 4. The results show that all indicators have outer loading values above 0.70, Cronbach's Alpha values above 0.90, Composite Reliability values above 0.90, and AVE values above 0.50, indicating that the measurement model is valid and reliable. The hypothesis test shows a path coefficient of 0.672, a t-statistic of 7.018, and a p-value of <0.001. The R Square value of 0.452 indicates that Social Media Public Relations explains 45.2% of the variation in Media Image. Therefore, Social Media Public Relations has a positive and significant influence on the Media Image of Bincang Perempuan among Generation Z.